James Mandrell, Don Juan and the point of honor: Seduction, patriarchal society, and literary tradition. Pennsylvania State University Press, University Park, PA, 1992; 310 pp. - Chorba, Carrie C. (El Colegio de México, 1996)
Se reseñó el libro: Don Juan and the point of honor: Seduction, patriarchal society, and literary tradition.